Focal therapies for retinoblastoma - Cieślik, Krzysztof; Rogowska, Anna; Hautz, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Currently, the primary treatment for retinoblastoma is intravenous and/or intraarterial chemotherapy. However, adjuvant focal therapies are also an essential component in the treatment of this cancer. The article discusses the methods of focal treatment of retinoblastoma: cryotherapy, transpupillary laser thermotherapy, transpupillary laser thermotherapy with intravenous indocyanine, brachytherapy, enucleation, and intraarterial and bicameral injections of melphalan. Particular attention is given to the latest methods of treatment including topical chemotherapy (intravitreal injections) and intraarterial chemotherapy. These modern topical treatments help salvage the eye in an increasing number of patients with advanced retinoblastoma.